AB0582 Atherosclerotic risk factors and upper respiratory inflammations of mpo-anca positive anca associated vasculitis. (15th June 2017) - Ono, N; Miyamura, T; Inoue, Y; Ueki, N; Miyake, K; Nagano, S; Inoue, H; Ueda, N; Oryoji, K; Sawabe, T; Yoshizawa, S; Takemoto, Y; et al.
Abstract : Background: Recent studies had proven that the genetic backgrounds of ANCA associated vasculitis (AAV) were dependent on ANCAs. We and other groups had shown the differences between MPO-ANCA positive Granulomatosis with polyangitis (MPO-GPA) and Microscopic polyangitis (MPA) (1–3). It is not clear what determine these two phenotypes. Objectives: To elucidate the etiologies of two phenotypes, we compared the backgrounds and comorbidities between MPO-GPA and MPA. Methods: Retrospectively we recruited MPO-GPA and MPA patients through the two multi-center cohorts (Cohort A: 2001–2012, Cohort B: 2012–2016). We classified patients with EMEA classification and ANCA. We found 40 MPO-GPA and 126 MPA cases without overlaps. We compared those backgrounds, comorbidities, organ involvements and outcomes. Results: The average age of MPO-GPA group was similar to that of MPA (69.1 years old vs 72.1 years old). But MPO-GPA preferentially affected female patients (80.0% vs 52.8%) with lower creatinine levels (1.03mg/dl vs 2.7mg/dl). Two year survivals of MPO-GPA were significantly better than MPA (95.8% vs 73.2%, p=0.0424). Interestingly MPO-GPA patients had less atherosclerotic risk factors, i.e. smoking history (6.3% vs 38.4%), hypertension (10.4% vs 30.5%) and diabetes (12.5% vs 17.9%). Instead these patients had more upper respiratory inflammations (chronic sinusitis, chronic otitis media and allergic rhinitis, 33.3% vs 6.6%) before the disease onset. Conclusions: We found that MPA had more atherosclerotic risk factors, and MPO-GPA had more upper respiratory inflammations. These factors may determine MPA or GPA phenotypes in MPO-ANCA positive AAV. References: Ono N at al. Characteristics of MPO-ANCA-positive granulomatosis with polyangiitis: a retrospective multi-center study in Japan. Rheumatol Int. 2015 Mar;35(3):555–9. Miloslavsky EM et al. MPO-ANCA-Positive and ANCA-Negative Patients With Granulomatosis With Polyangiitis (Wegener's): Distinct Patient Subsets. Arthritis Rheumatol. 2016 Dec;68(12):2945–2952. Schirmer JH at al. MPO-ANCA-Positive Granulomatosis With Polyangiitis (Wegener's) Is a Clinically Distinct Subset of ANCA-Associated Vasculitis: A Retrospective Analysis of 315 Patients From a German Vasculitis Referral Center. Arthritis Rheumatol. 2016 Dec;68(12):2953–2963. Acknowledgements: We gratefully acknowledge the work of people who helped to correct patients data. Disclosure of Interest: None declared